ANALISIS KESESUAIAN ANTARA LATAR BELAKANG PENDIDIKAN GURU MADRASAH IBTIDAIYAH DENGAN MATA PELAJARAN YANG DIAMPU - Samsul Bahri (Program Studi Pendidikan Matematika, STKIP Bina Bangsa Getsempena, 2019)
Teachers must have academic qualifications and educational backgrounds in accordance with the field of duty. The teacher as a professional means that the teacher's work can only be done by someone who has academic qualifications, competencies, and educator certificates in accordance with the requirements for certain types and levels of education. The objectives of the research in this study are: To what extent is the degree of conformity between the education background of the Madrasah ibididaiyah teachers and elementary schools in the North Aceh environment with the subjects taught. In this study using qualitative research. The conclusions were that there were 27.86% or as many as 102 out of 366 teachers who had educational backgrounds that were not in accordance with heresy skills. Many factors influence the teachers of madrasah ibtidaiyah and elementary schools in the North Aceh environment in teaching subjects are: